Selection of maize lines and prediction of hybrid and synthetic means using intergroup topcrosses - Costa,Nayana Valéria (2022)
Abstract Topcrosses are routinely used in maize-hybrid programs. This study aimed to evaluate heterosis components and combining ability to predict hybrid means between synthetics from two groups of S1 maize lines using the intergroup topcrosses model that includes S2 lines. Two groups, each with 30 S1 maize lines, were crossed using an intergroup topcross system, with a mixture of lines from one group as a tester for the contrasting group. Simultaneously, 30 S2 lines from each group were generated via self-pollination. Lines and topcrosses were experimentally evaluated and the data were analyzed using a model adapted to the study design. The results showed the suitability of the proposed model for studying heterosis components and general combining ability, detailing additive and dominance effects. Prediction of hybrid means between synthetics showed the potential of the lines to generate base populations for an interpopulation breeding program.